Use of progestins to inhibit spontaneous ovulation during ovarian stimulation: the beginning of a new era?. Issue 2 (August 2019) - La Marca, Antonio; Capuzzo, Martina
Abstract: Advances in oocyte and embryo cryopreservation for assisted reproduction prompted new approaches to ovarian stimulation. Attention has been paid to progesterone and its derivatives to block the LH surge, as oocyte vitrification removes possible harmful effects of progestins on endometrial receptivity. This review summarizes the current status of progestin use to inhibit ovulation during ovarian stimulation compared with conventional ovarian stimulation. Progestin-primed ovarian stimulation is shown to effectively inhibit spontaneous ovulation, without affecting the number of retrieved oocytes and embryo quality. Reproductive outcomes from ovarian stimulation with progestins appear similar to those from conventional ovarian stimulation, although large trials are needed to confirm this. Use of progestins allows better control of LH concentrations, lower costs and easier (oral) administration. Therefore, progestin-primed ovarian stimulation could be the first choice for ovarian stimulation in fertility preservation, oocyte donation and preimplantation genetic testing cycles. So-called 'non-conventional' ovarian stimulation protocols (luteal and random-start, double ovarian stimulation), which always require oocyte or embryo cryopreservation, may also use progestins to inhibit the endogenous LH surge. Since the 'freeze-all' strategy with delayed transfer is mandatory, high responders undergoing IVF could benefit more from this approach. Economic advantage remains to be demonstrated, as do pregnancy and neonatal outcomes.